2020
DOI: 10.3389/fpsyg.2020.00119
|View full text |Cite
|
Sign up to set email alerts
|

Two Cultural Models on Infant Motor Development: Middle Class Parents in Israel and the Netherlands

Abstract: Culture influences the way parents shape children's environment. Two studies examined cross-cultural differences in parental practices related to motor development in Israel and the Netherlands. In the first study, 198 Dutch and 206 Israeli parents of infants aged 1-7.5 months completed questionnaires measuring parental practices and beliefs regarding motor development. In the second study, 30 Dutch and 30 Israeli parents completed the same questionnaires when their children were 2 and 10 months old. While sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Asthmatic attacks, allergic reactions, and infections (from any over 40 types of pathogens) can also be triggered by bed bug infestations, another health hazard found in this study, whereby multiple occupiers were found to use the same mattress for various lengths of time [ 39 , 63 ]. U5TA were often found to be left in a buggy or pram as a safety provision because of lack of space and other hazards (e.g., mold, pests/vermin), but this can critically hamper development and meeting health milestones, even posing a significant and powerful risk for progression to a neurodevelopmental disorder or syndrome if not addressed [ 64 , 65 ]. Broken windows, structural problems/disrepair, unsafe electrics, staircases with a change in level greater than 300 mm, and the lack of safety provision (e.g., baby/child safety gates) were all found in this study and increase the risks of injury, collision or entrapment in addition to being markers of social deprivation and health inequality [ 39 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asthmatic attacks, allergic reactions, and infections (from any over 40 types of pathogens) can also be triggered by bed bug infestations, another health hazard found in this study, whereby multiple occupiers were found to use the same mattress for various lengths of time [ 39 , 63 ]. U5TA were often found to be left in a buggy or pram as a safety provision because of lack of space and other hazards (e.g., mold, pests/vermin), but this can critically hamper development and meeting health milestones, even posing a significant and powerful risk for progression to a neurodevelopmental disorder or syndrome if not addressed [ 64 , 65 ]. Broken windows, structural problems/disrepair, unsafe electrics, staircases with a change in level greater than 300 mm, and the lack of safety provision (e.g., baby/child safety gates) were all found in this study and increase the risks of injury, collision or entrapment in addition to being markers of social deprivation and health inequality [ 39 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, parental beliefs seem to play a role in expectations of development [ 40 , 41 ]. In our study, first-time parents felt that they should actively stimulate their child's motor development, while experienced parents were happy to trust their infant's own pace.…”
Section: Discussionmentioning
confidence: 99%
“…Parents’ expectations inform how infants should be handled, where they should be placed, and how much agency they should be allowed in their daily lives. Moreover, parents have culture-specific expectations about what skills infants should acquire and when and adjust their practices to meet those expectations (Gomes et al, 2017; Oudgenoeg-Paz et al, 2020). It is in the context of these handling practices caregivers evaluate the health and wellbeing of their babies and whether they are developing according to their cultural expectations.…”
Section: Cultural Considerations For Policymentioning
confidence: 99%